Barriers to ART adherence among school students living with HIV in Kenya. Issue 3 (3rd July 2021) - Apondi, Edith; Wachira, Juddy; Ayikukwei, Rose; Kafu, Catherine; Onyango, Jael; Omollo, Mark; Genberg, Becky; Nyandiko, Winstone; Braitstein, Paula
Abstract : HIV has transformed from a serious acute illness with high rates of morbidity and mortality to a fairly easily managed chronic disease. However, children and adolescents living with HIV are yet to achieve similar improvement in their HIV care outcomes compared to adults. There have been a number of studies assessing the reasons for slower improvement in these age categories, mainly focusing on health systems, drug- and family- related barriers to ART adherence in children. We sought to explore school-related barriers to adherence through in-depth interviews with students living with HIV (SLHIV) aged 13–17 years who had fully disclosed their HIV status in western Kenya. Data was analysed using NVivo 8™. The study found that stigmatisation in the form of negative discussions and alienation, fear of unintended disclosure (due to the drug packaging and lack of privacy while taking their pills) were barriers to ART adherence among these SLHIV. Other barriers included challenges with drug storage while in school and the complexity of coordinating school and clinic-related activities and a lack of structured support systems in schools. In addition to hindering their adherence to ART, these barriers resulted in negative emotions (anger, sadness, frustration) and affected school performance. This study found fairly serious barriers to ART adherence among SLHIV, which calls for structured communication and coordinated support between government ministries of health and education in Kenya.